A national profile of substance use disorder among Medicaid enrollees on the autism spectrum or with intellectual disability. Issue 2 (June 2022) - Roux, Anne M.; Tao, Sha; Marcus, Steven; Lushin, Viktor; Shea, Lindsay L.
Abstract: Background: Recent research has questioned the assumption that people with intellectual disability (ID) or autism spectrum disorder (ASD) are less at risk of substance use disorders (SUDs). Overall, little is known about SUDs among people with intellectual and developmental disabilities (/IDDs). Objective: This study aimed to estimate prevalence of SUD among Medicaid enrollees with ASD, ID, or ASD + ID; characterize these groups and types of SUDs; and identify risk of SUD by demographic and clinical characteristics within groups. Methods: We used 2008–2012 national Medicaid data to identify enrollees with ASD, ID, ASD + ID and a sample without ASD/ID and identified SUDs within these individuals. We used descriptive statistics to characterize enrollee groups and types of SUDs, calculated SUD prevalence, and used modified Poisson regression to examine adjusted relative risk of SUD within disability groups. Results: SUD prevalence increased yearly across disability groups to 1–2.2%, increasing most quickly among those with ASD. Alcohol abuse was the most common SUD among those with ID-only (57%) versus cannabis abuse among the ASD-only group (41%). Risk of SUD was higher among those with co-occurring psychiatric disorders – notably, depression. Conclusions: Results highlight increasing prevalence of SUD among Medicaid enrollees with ASD-only and ASD + ID and higher risk of SUD among those with depression and other psychiatric disorders. Understanding access to screening, diagnosis and treatment of SUD among people with I/DDs is a highly important question for future research.